(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
We have seen the incorporation of Literature in an assortment of controls. Multidisciplinary studies’ and ’multiculturalism’ being key terms in the scholarly community—mostly in the Social Sciences and the Humanities—different college disciplines have begun reinforcing their schedules toward this path. This paper contends that a solitary disciplinary methodology neglects to address an abstract custom and standard in Leadership Studies. It centers around consideration of Literature into the control. The initial segment manages a short presentation on the incorporation of Literature in Leadership contemplates pursued by how Shakespearean writings can be utilized as contextual analyses to train leadership issues. The paper contends that abstract writings help in creating alternate points of view and understanding various issues in leadership. A concise audit on the speculations of leadership is fused to upgrade the comprehension of the pith of leadership. The paper finishes up with an accentuation on the consideration of artistic messages in Leadership Studies to advance better comprehension of the issues in leadership.